Hubungan Aktivitas Fisik Sehari-hari dengan Derajat Hipertensi pada Pra Lansia dan Lansia di Wilayah Kerja Puskesmas I Denpasar Timur - Ni Putu Ayu Indah Eliani; Luh Gede Sri Yenny; Ni Made Hegard Sukmawati (Aesculapius Medical Journal, 2022)
Abstract The majority of cardiovascular diseases in community, especially the elderly are hypertension. One of the effective non-pharmacological of hypertension is physical activity. The purpose of this study to determine the relationship of daily physical activity with the degree of hypertension in the pre-elderly and elderly in ​​Puskesmas I East Denpasar. This research used observational analytic research method with cross sectional and consecutive sampling technique. The instrument used in this study were the GPAQ questionnaire, sphygmomanometer and stethoscope. Data analysis was carried out in this research Spearman rank test. The research sample amounted to 64 samples. The results showed that there were 10 samples (15.6%) with low physical activity experienced hypertension, 1 of them (1.6%) had first degree hypertension, 3 samples (4.7%) had second degree hypertension and third degree hypertension was 6 samples (9.4%). A total of 35 samples (54.7%) who were physically active were experiencing hypertension including first degree hypertension as many as 21 samples (32.8%), second degree hypertension as many as 11 samples (17.2%), and third degree hypertension as many as 3 (4,7%). Of the total 19 samples (29.7%) who had high physical activity, 16 samples (25%) had first degree hypertension, 2 samples (3.1%) had second degree hypertension and 1 sample had third degree hypertension (1.6%). Based on the results of the Spearman rank, it is known that there is a significant relationship between daily physical activity and the degree of hypertension in the pre-elderly and elderly at Puskesmas I East Denpasar (p-value 0.0001) with a non-unidirectional relationship (r=-0.489). The increasing physical activity, the lower the degree of hypertension on the sample.